Business Psychology and Organizational Behaviour - Eugene F. McKenna (New York Routledge, 2020)
Business Psychology and Organizational Behaviour introduces principles and concepts in psychology and organizational behaviour with emphasis on relevance and applications. Well organised and clearly written, it draws on a sound theoretical and applied base, and utilizes real-life examples, theories, and research findings of relevance to the world of business and work. The new edition of this best-selling textbook has been revised and updated with expanded and new material, including: proactive personality and situational theory in personality; theory of purposeful work behaviour; emotional and social anxiety in communication; decision biases and errors; and right brain activity and creativity, to name a few. There are numerous helpful features such as learning outcomes, chapter summaries, review questions, a glossary, and a comprehensive bibliography. Illustrations of practice and relevant theory and research also take the reader through individual, group, and organizational perspectives. This is an essential textbook for undergraduates and postgraduates studying psychology and organizational behaviour. What is more, it can be profitably used on degree, diploma, professional, and short courses. It's also likely to be of interest to the reflective practitioner in work organizations.
Keywords: Business; Psychology; (UGB107) Introduction to Business Management; (UGB261) Management Thought; Business Psychology (HRM1089-N)